The overlooked role of UV185 induced high-energy excited states in the dephosphorization of organophosphorus pesticide by VUV/persulfate - Yudan Liu; Jingke Wu; Nanchunxiao Cheng; Pengfei Gan; Yunyi Li; Liu, Wen; Jiangyu Ye; Meiping Tong; Jialiang Liang (Chemosphere, 2023)
Vacuum ultraviolet (VUV) based advanced oxidation processes (AOPs) recently attracted widespread interests. However, the role of UV185 in VUV is only considered to be generating a series of active species, while the effect of photoexcitation has long been overlooked. In this work, the role of UV185 induced high-energy excited state for the dephosphorization of organophosphorus pesticides was studied using malathion as a model. Results showed malathion degradation was highly related to radical yield, while its dephosphorization was not. It was UV185 rather than UV254 or radical yield that was responsible for malathion dephosphorization by VUV/persulfate. DFT calculation results demonstrated that the polarity of P-S bond was further increased during UV185 excitation, favoring dephosphorization while UV254 did not. The conclusion was further supported by degradation path identification. Moreover, despite the fact that anions (Cl-, SO42- and NO3-) considerably affected radical yield, only Cl- and NO3- with high molar extinction coefficient at 185 nm significantly affected dephosphorization. This study shed light on the crucial role of excited states in VUV based AOPs and provided a new idea for the development of mineralization technology of organophosphorus pesticides.
Keywords: Excited state; Mineralization; Photoexcitation; Radical yield; VUV